Learning Procedures as the Basic Skill for the Upskill in STEM Education - Ann Ngozi Ugobueze (PT. Pusmedia Group Indonesia, 2025)
Education is the root of all skills and human advancement. Learning is permanent change in behavior, learning can be acquired through formal, non formal and informal education but the greatest of all is formal education where reading and writing skills are acquired for the acquisition of other skills. This paper seeks to highlight on the pre-learning procedures for learning and skills advancement. The learning challenges, learning boosters and principles are highlighted; conclusion is drawn for the upskill in stem education.